CAPTURA DE CARBONO EN EL VERTEDERO MUNICIPAL DE LA CIUDAD DE ENCARNACIÓN, DEPARTAMENTO DE ITAPÚA, PARAGUAY (Journal on studies and research of academic knowledge, 2008)
This study looks forward to estimate the amount of methane generated in the current Municipal Landfill in Quiteria, Encarnación, Paraguay. This city has a population of 70,000 inhabitants and is located in the southern Department of Itapúa. The proposed activity means the beginning of future actions to be implemented in order to reduce emissions of Greenhouse Gases (GHG) wich generate Emission Reduction Credits (RCES) and local benefits such as job creation during the construction, operation and maintenance, and the possibility of using biogas as a renewable energy in companies. The hypothesis is that there is great potential for generating revenue to the City of incarnations through proper management of sanitary landfills and implementation of a draft Clean Development Mechanism (CDM), with which the captured carbon will generate Emission Reduction Credits (RCES) and environmental benefits to the Municipality.
Keywords: Greenhouse gases; Municipal Landfill; Methane; Remainders; Organic Matter; Biogas; Carbon Capture; Clean Development Mechanism; Emissions Reduce Credits